2013
DOI: 10.3329/bjar.v38i2.15885
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic And Phenotypic Correlation And Path Analysis In Durum Wheat (Triticum turgidum L. var. durum)

Abstract: An experiment was conducted at Regional Agricultural Research Station, Ishurdi during the 2009-10 cropping season with the objective of estimating the associations between yield and yield-related traits and to identify direct and indirect effects of characters on grain yield in durum wheat. The result showed significant variation among the genotypes for all the characters studied. Significant positive correlation was found for plant height, number of spikes/m2 and 1000-grain weight with grain yield. Heading da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…Similar results were also reported by Khan et al (2013) and Tadesse et al (2016). Higher magnitude of genotypic correlation helps in selection for genetically controlled characters and gives a better response for seed yield improvement than that would be expected on the basis of phenotypic association alone (Robinson et al 1951).…”
Section: Correlation Coefficient Analysissupporting
confidence: 75%
“…Similar results were also reported by Khan et al (2013) and Tadesse et al (2016). Higher magnitude of genotypic correlation helps in selection for genetically controlled characters and gives a better response for seed yield improvement than that would be expected on the basis of phenotypic association alone (Robinson et al 1951).…”
Section: Correlation Coefficient Analysissupporting
confidence: 75%
“…Increasing in traits PLH, SL, TKW and PL can improve GY potential in durum wheat genotypes. Golparvar et al (2006), De Vita et al (2007 and Khan et al (2013) have reported relatively similar results for breeding these traits that are emphasised in this research for genetic improvement of GY. Also, the studied durum wheat genotypes would probably have evolved to highlight the most efficient mechanisms for GY production under water-stressed conditions.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, breeding under marginal environments has indicated that some agronomical traits when mea-T a b l e 6 Summary of factors loading for measured traits of durum wheat genotypes in both non-stressed and water-stressed conditions Abbreviations see Table 1 Non-stressed condition Water-stressed condition sured in drought-stressed condition were associated with yield performance in durum-wheat growing regions worldwide (Zarei et al 2013). Morphological traits associated with increased GY potential in durum wheat include yield components and harvest index (Khan et al 2013). We found, while TKW can be used as a guide to selection, the other traits are less effective.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Many studies on wheat productivity have attributed yield gains to a number of parameters. Yield component concept in breeding has much importance in improving yield potentiality (Khan et al, 2013). Some studies indicated that the component most affecting wheat productivity is grain number per spike (Avcin et al, 1997) and grain number per square meter (Donmez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%